Validation of the Indonesian Version of the Asian Diabetes Quality of Life Questionnaire - Hikmat Permana; Michelle Vincentia Liem; Nanny N. M. Soetedjo (Acta Medica Indonesiana, 2021)
Background: quality of life has been identified as the goal of therapy especially in patient with chronic disease such as type 2 diabetes mellitus. Quality of life measurement requires an instrument that was specifically developed in accordance with socio-cultural background of the measured population. The aim of this study was to adapt Asian Diabetes Quality of Life Questionnaire so it can be used in Indonesia as valid and reliable tool. Methods: Asian Diabetes Quality of Life Questionnaire was translated and adapted by group of experts, then validity and reliability tests were conducted on type 2 diabetes mellitus patients at Dr. Hasan Sadikin General Hospital, Bandung. Construct validity was analyzed using correlation test between score of each item and total score. Reliability was measured using test-retest method and internal consistency represented in Cronbach’s alpha score. Results: validity test showed significant correlation (p-value ≤0.05) between score of each item and total score across all domains with moderate to very strong correlation (r: 0.496-0.956). Reliability test using test-retest method showed no significant difference between Test I and II results (p-value >0.05) with very strong correlation (r: 0.830-0.975) and internal consistency yielded Cronbach’s alpha scores of  ≥ 0.07 for all domains. Conclusion: Indonesian version of Asian DQOL is a valid and reliable tool to measure quality of life of type 2 diabetes mellitus patients.